Parasitic lung infections: nematodes - Vijayan, Vannan Kandi (Henry Stewart Talks, 2013)
Protozoal and helminthic parasites cause significant lung diseases, Eosinophilia occur mainly in helminthic infections, Immunosuppressed individuals are prone to develop serious parasitic lung infections, Parasitic lung infections mimics many common and uncommon lung diseases, Effective antiparasitic drugs are available, Prevention of many parasite infections are by proper personal hygiene, consuming properly cooked food and avoiding bites from mosquitoes, ticks and flies